Pengembangan Aplikasi Augmented Reality Gerak Dasar Tari Legong Pada Uang 50 Ribu - Pratama, I Putu Dimas Wiraputra; Wahyuni, Dessy Seri; Damayanthi, Luh Putu Eka (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This research is motivated by the limited availability of interactive educational media for introducing the basic movements of the Legong Dance in Buleleng Regency, resulting in the public particularly the younger generation lacking adequate understanding of this classical Balinese dance. The purpose of this study is to develop an Augmented Reality–based learning application called iLegong, using a fifty-thousand-rupiah banknote as a marker, and to evaluate the feasibility, quality, and user experience of the resulting application. The study was conducted in Buleleng Regency using a Research and Development approach with the Multimedia Development Life Cycle model, which consists of six development stages: concept formulation, design planning, material collecting, assembly, testing, and distribution. User experience testing was carried out using the User Experience Questionnaire administered to forty respondents. The results show that the iLegong application was successfully developed, featuring three-dimensional visualizations of Legong Dance basic movements, supporting text, audio, and responsive interactions. Content and media expert assessments indicated a very high level of feasibility, while user experience evaluations placed all dimensions in the “very good” category, with the attractiveness aspect obtaining the highest score. These findings demonstrate that iLegong is suitable as an effective interactive learning medium for introducing the basic movements of the Legong Dance and holds potential for further development across various Balinese dances as well as cross-platform implementation.